Optimizing spectral utilization of LPWANs - Jathun Gamage Isuru Amalinda (Nanyang Technological University, 2023)
The emergence of the Internet of Things (IoT) has been pivotal in advancing urban and industrial efficiency, largely enabled by the growth of long-range low-power wide-area networks (LPWANs). These networks have facilitated IoT integration into diverse applications, including environmental monitoring, traffic control, and smart metering. In the LPWAN domain, LoRa modulation stands out for its long-range communication capabilities, addressing challenges posed by the rapid expansion of IoT devices. Despite being relatively new, LoRa has rapidly expanded to nearly 150 countries, redefining LPWAN standards. However, there is significant potential for further optimization. This thesis focuses on enhancing LoRa networks. First we identify a fundamental limitation in current LoRa networks: their reliance on the basic ALOHA mechanism for media access control, a result of LoRa's lack of carrier sense capability. Our research reveals that the recently introduced channel activity detection feature in LoRa, initially aimed at energy-efficient preamble chirp detection, can also reliably detect payload chirps. This discovery leads to the development of an efficient carrier-sense multiple access protocol, named LMAC, tailored for LoRa networks.